Foresight tool for nutrition management practice in Vietnam - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Stage 1: Research: Discovery the relationship between climate change and nutrition indicators; it will expand to other indicators in food system concept. NIN has shared the raw database on General Nutritiion survey 2009-2010 and Nutrition Surveillance in 2012-2013-2014-2015